Considerations on the Fortresses Toponyms from High Middle Ages until Today - PaÃ§o, Eliana (Mediterranean Journal of Social Sciences, 2012)
In the focus of the article are presented some of toponyms in the book of Prokopio of Cesarea "De Aedificiis" whichrefer to their strongholds or places situated near the Illyrian and Epirotic settlements. Different authors have noticed that in somecases, the toponyms are not associated with archaeological correct data and some of them are written with linguistic mistakes.These two gaps make it difficult analysis undertaken, but not impossible. On its part, the author of the article, has tried, alsorelying on other historical sources and various studies made by albanologists of different times, to give its opinion on thesetoponyms and achieve the important conclusions.